Differential CD4+ cell count increase and CD4+ : CD8+ ratio normalization with maraviroc compared with tenofovir. (24th August 2016) - Chan, Ellen S.; Landay, Alan L.; Brown, Todd T.; Ribaudo, Heather J.; Mirmonsef, Paria; Ofotokun, Igho; Weitzmann, M. Neale; Martinson, Jeffrey; Klingman, Karin L.; Eron, Joseph J.; Fichtenbaum, Carl J.; Plants, Jill; et al.
Abstract : Objective: Studies exploring the immunologic effects of maraviroc (MVC) have produced mixed results; hence, it remains unclear whether MVC has unique immunologic effects in comparison with other antiretroviral drugs. We sought to determine whether MVC has differential effects compared with tenofovir disoproxil fumarate (TDF) during initial antiretroviral therapy. Design: Prospective study in AIDS Clinical Trials Group A5303, a double-blind, placebo-controlled trial ( N = 262) of MVC vs. TDF, each combined with boosted darunavir and emtricitabine. Methods: A total of 31 cellular and soluble biomarkers were assayed at weeks 0 and 48. Polychromatic flow cytometry was performed on cryopreserved peripheral blood mononuclear cells. Soluble markers were assayed in plasma using ELISA kits. Analyses were as treated. Results: Analyses included 230 participants (119 in MVC arm and 111 in TDF arm). Over 48 weeks of treatment, no significant differences were detected in declines in markers of inflammation and activation with MVC vs. TDF. A greater CD4 + T-cell count increase (median +234 vs. +188 cells/μl, P = 0.036), a smaller CD8 + T-cell count decrease (−6 vs. −109 cells/μl, P = 0.008), and a smaller CD4 + : CD8 + ratio increase (0.26 vs. 0.39, P = 0.003) occurred with MVC. Among participants with a baseline CD4 + : CD8 + ratio less than 1, a smaller proportion of MVC group normalized to a ratio greater than 1 at week 48 (15 and 36%, P < 0.001). Conclusion: MVC resulted in less improvement in the CD4 + : CD8 + ratio driven by greater increase in CD4 + cell count but smaller decline in CD8 + cell count. Changes in soluble or cellular biomarkers of inflammation and immune activation were not different between MVC and TDF.